Age-Related Features of Mast Cell Reactivity in Allergies - Sattar Begmanov1, Y. Zokirov1, N. Abidova1, G. Khakimova1, Z. Shakhobutdinov1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: During last few years, a novel scientific sphere has developed and is successfully growing,associated with the study of age-related changes in immune and allergic reactions at the cellular level.Although there is a fact that mast cells are the subject of many researches, many aspects of their physiologyand pathology remain unsolved. Moreover, clarification in the age-related features of mast cell reactivitymakes a great contribution to the expansion of our view of point on the characteristics of the clinic, etiologyand pathogenesis of allergies in ontogenesis.Materials and Method: We used 443 guinea pigs of both sexes of different ages, previously experienced 10-14 day-quarantine control under conditions of vivariums. Animals were constantly monitored, body weightwas periodically determined, and rectal temperature was measured. Sensitization and anaphylactic reactionswere reproduced by conventional method. Normal horse serum was used as an allergen. The resolving doseof a specific allergen was administered once intravenously or intraperitoneally 14-16 days after the startof the first sensitizing dose of the allergen. Collected digital data processed on electronic microcalculatorRokwell international Model 44 (USA).Results: With age, the rate of filling mast cells with granules increases. In guinea pigs of an older age, ascompared to newborns, the rates of filling mast cells with granules are 1.3-2.2 times greater (p <0.05), whichis consistent with the literature. Spontaneous mast cell degranulation was observed in intact animals. Theirfrequency ranged from 5.4 to 8.6% and, in principle, did not depend on age. A comparative analysis of thefrequency of degranulation, depending on age, showed that the frequency of degranulation in sensitizednewborns is slightly lower than in older animals. However, with age in sensitized guinea pigs, the frequencyof degranulated mast cell forms increased and the mast cell reactivity in one month aged pigs becameapproximately the same as in mature animals.Conclusion: In general, the functional activity of mast cells increases with age, and by the age of one monthreaches the level of functional activity. In the development of specific therapy, a decrease in the titer ofhomocytotropic antibodies and the percentage of mast cell degranulation is vital.